Objectification of women in carnival Calabar: an emerging paradigm - Edisua Merab Yta (International Journal of Humanities and Innovation (IJHI), 2020)
A trend that is developing in Carnival Calabar is the objectification of women. Carnival Calabar is a festival that brings families together. Most of the participants are young people. What messages is Carnival Calabar selling to its various publics and what influence do these messages have on the young population? To answer these questions, two descriptive methodologies were employed in this study. The first was content analysis which comprised of pictures, participant observation and on-site participatory interviews. The second was the survey which comprised of focus group discussion. The following findings were made that the Carnival Calabar nude images portray women in her traditional role and sexual appeal to men. Secondly, Carnival Calabar's sexualized images often make girls lose their self-esteem. It is recommended that Carnival Calabar develop its unique brand of Carnival without following the Caribbean and other nations' models which one of its distinctions is parading nude female bodies. Carnival Calabar content should portray women constructively and in a wider variety of positive roles. It is recommended that more women should be involved as scriptwriters, producers, designers and in the position of decision making within the state’s tourism industry to influence the messages of women portrayed in Carnival Calabar.